The impact of school-based nutrition interventions on parents and other family members: a systematic literature review - Abderbwih, Eman; Mahanani, Melani Ratih; Deckert, Andreas; Antia, Khatia; Agbaria, Nisreen; Dambach, Peter; Kohler, Stefan; Horstick, Olaf; Winkler, Volker; Wendt, Amanda (Nutrients, 2022)
Little is known about the impact of school-based nutrition interventions on parents and other family members. This systematic review aims to explore the impact of school-based nutrition interventions on different parental/family outcomes, mainly dietary intake, nutrition knowledge, and health outcomes. PubMed, Web of Science, PsycINFO, EconLit, Cochrane Reviews, and Google Scholar were systematically searched for controlled trials or natural experiments measuring the impact of school-based nutrition interventions, with or without parental involvement, on parents/families of school children. Twenty-two studies met the inclusion criteria. Of which, 15 studies assessed the impact of school-based nutrition interventions on parental/family dietary intake, 10 on parental/family nutrition knowledge, and 2 on parental/family health outcomes. Inconsistent results were found for parental dietary intake with six studies reporting favorable effects. Most studies found improved parental nutrition knowledge. Positive impacts were seen by both studies that assessed the impact on a parental health outcome. Overall, we found that there is potential for school-based nutrition interventions to result in positive effects for parents, in particular for nutrition knowledge. More research is needed to assess the impacts of school-based nutrition interventions on parents and other family members and to assess important intervention characteristics in creating a positive impact.
Gesehen am 06.07.2022